Cultural barriers in German-Spanish business communication - Mateo González, Raquel (Glottodidactica, 2018)
This research project aims at identifying and describing possible critical incidents which may arise in the framework of transcultural discursive practices between professionals from Germany and Spain in business situations, for example, in interviews, meetings, negotiations, and decision making. The methodology employed in this paper is based on an empirical study using by means of personal interviews and questionnaires in order to defend or refute cultural standards in the business world existing in established theoretical foundations.